CHSE Rafting Guide Implementation Analysis in the New Normal Era on Payung Rafting Tourism Object - Ni Luh Gede Aris Maytadewi Negara; Putu Vierda Lya Suandari (Babali Nursing Research, 2022)
Introduction: The development of the tourism sector in Indonesia is so fast, but since the COVID-19 pandemic, tourist visits have decreased. In the new normal era, there is a change in behavior to continue to carry out activities by implementing health protocols. Several tourist attractions began operating with the implementation of health protocols. The government issued guidelines for the implementation of Cleanliness, Health, and Safety Environmental Sustainability (CHSE). CHSE rafting tour is guided to meet the needs of tourists for clean, healthy, safe, and environmentally friendly tourism products and services during the COVID-19 pandemic. Payung Rafting Managers try to implement health protocols to the maximum. This study was conducted to determine the extent to which Payung Rafting managers apply the CHSE Guidelines. Methods: This research is quantitative study with cross sectional design. Analysis of the fulfillment of the CHSE rafting guidelines at the Payung Rafting tourist attraction was carried out, using the CHSE rafting instrument released by the Ministry of Tourism and Creative Economy. This activity has been carried out on August 9, 2021. Results: The results showed that Payung Rafting was able to meet 69% of the CHSE guidelines, while based on the results of the Pearson Chi-Square test, a value of 0.119 was obtained with a significance value of 0.730 (p> 0.05). Conclusion: This study statistically shows there is no difference between the CHSE guidelines and implementation in Payung Rafting, but descriptive analysis shows that Payung Rafting can apply 69% of the CHSE guidelines.